2019
DOI: 10.3389/fcimb.2019.00105
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cell-Dependent Macrophage Activation Modulates Sustained PS Exposure on Intracellular Amastigotes of Leishmania amazonensis

Abstract: Leishmania amazonensis amastigotes can make use of surface-exposed phosphatidylserine (PS) molecules to promote infection and non-classical activation of macrophages (MΦ), leading to uncontrolled intracellular proliferation of the parasites. This mechanism was quoted as apoptotic mimicry. Moreover, the amount of PS molecules exposed on the surface of amastigotes correlates with the susceptibility of the host. In this study, we tested whether host cellular responses influence PS expression on intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…[21][22][23]. An effective vaccine must also induce the development of an antiparasitic CD4 + and CD8 + T-cell-mediated Th1 immunity, which is characterized by the production of interferon-γ (IFN-γ), interleukin-2 (IL-2) and IL-12, among other pro-inflammatory cytokines [24,25]. On the other hand, susceptible murine models, such as the BALB/c mice model of CL induced by L. amazonensis, are associated with the development of a Th2-type response, with high levels of parasite-specific induction of IL-4 and IL-10 along with elevated antileishmanial immunoglobulin G1 (IgG1) antibody production [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23]. An effective vaccine must also induce the development of an antiparasitic CD4 + and CD8 + T-cell-mediated Th1 immunity, which is characterized by the production of interferon-γ (IFN-γ), interleukin-2 (IL-2) and IL-12, among other pro-inflammatory cytokines [24,25]. On the other hand, susceptible murine models, such as the BALB/c mice model of CL induced by L. amazonensis, are associated with the development of a Th2-type response, with high levels of parasite-specific induction of IL-4 and IL-10 along with elevated antileishmanial immunoglobulin G1 (IgG1) antibody production [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…IL-12 is a key cytokine that induces the T-helper 1 (Th1) response which is essential for parasite elimination in infected macrophages [44][45][46]. It has been shown that the outcome of Leishmania infection in macrophages depends on their activation status [42,[47][48][49]. Classical activation of macrophages is mediated by Interferon gamma (IFN-γ), an effector cytokine secreted by CD4 + T helper type 1 (Th1) cells, CD8 + T cells, and natural killer (NK) cells [50].…”
Section: Macrophagesmentioning
confidence: 99%
“…Amastigote forms are adapted to the higher temperatures and lower pH encountered in mammalian hosts; therefore, they should not display apoptotic features in these conditions [33,34]. However, when purified from mice lesions or macrophages in in vitro cultures, amastigotes expose PS in the outer leaflet of the plasma membrane, despite the maintenance of viability, morphology, and ability to infect other cells, animals, phlebotomine sandflies and to differentiate into promastigote forms [5,[35][36][37]. This observation led to the question whether PS exposure on amastigotes plays a role in the normal biology of the parasite, unrelated to cell death.…”
Section: Leishmania Amazonensismentioning
confidence: 99%
“…It was observed that the recognition of PS on the surface of these parasites is fundamental for amastigote uptake by macrophages and, most importantly, to induce a permissive status in the host cell, allowing parasite intracellular growth and maintenance [5,[35][36][37]. During amastigote infection, PS is able to induce TGF-β1 and IL-10 production by macrophages, which decreases NO production [5,35,36]. Actually, the events triggered by PS recognition on amastigotes are similar to the ones observed during apoptotic cell recognition, as depicted in Fig.…”
Section: Leishmania Amazonensismentioning
confidence: 99%
See 1 more Smart Citation